A SELECTION AND EVALUATION OF PHYSICS AND CHEMISTRY CONCEPTS TO BE USED IN THE SEVENTH AND EIGHTH GRADE SCIENCE PROGRAM. - Cantrell, Sue Rowe; Caldwell, Loren T. (Science Education, 1963)
The article discusses the results of a research which evaluates physics and chemistry concepts to be used in the seventh and eighth grade science program in the United States. Since the junior high school student already has an advanced knowledge of science gained from mass media, the curriculum must be revised to lead the student into the more advanced phases of sciences. Teachers must let students acquire as early as possible the facts, concepts, principles and appreciations through which he can better understand and appreciate the world of the present time.